MASTERING BY STUDENTS OF THEMATIC SECTIONS OF MORAL PHILOSOPHY AS PART OF THE COURSE “PSYCHOLOGY OF EDUCATION” - I. B. Suslova (Science and Innovation Center Publishing House, 2019)
The article contains a block of questions developed by the author as part of the course “Psychology of Education”, relating to the field of ethics and moral philosophy. These questions, being part of the practical classes, are aimed at activating the spiritual and moral component in the students’ minds. As a result of familiarization of students with the subsequent sections, conversations and listening to the thematic cycle, is expected an increase in students’ motivation for personal self-actualization, self-knowledge, appropriation of value paradigms of ethics and moral philosophy.